2004
DOI: 10.1128/jvi.78.22.12625-12637.2004
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of the Glycan Shield of theHuman Immunodeficiency Virus Envelope during Natural Infection andImplications for Exposure of the 2G12Epitope

Abstract: Elucidation of the kinetics of exposure of neutralizing epitopes on the envelope of human immunodeficiency virus type 1 (HIV-1) during the course of infection may provide key information about how HIV escapes the immune system or why its envelope is such a poor immunogen to induce broadly efficient neutralizing antibodies. We analyzed the kinetics of exposure of the epitopes corresponding to the broadly neutralizing human monoclonal antibodies immunoglobulin G1b12 (IgG1b12), 2G12, and 2F5 at the quasispecies l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 53 publications
0
54
1
Order By: Relevance
“…Unlike 92UG037.8, CZA97.012 gp120 lacks a glycan at residue 295. This glycan site is generally considered to be one of the principal components of the 2G12 epitope (58)(59)(60)(61)(62)(63). Nonetheless, we observed that 2G12 could still bind efficiently to the CZA97.012 Env proteins in the SPR assay (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…Unlike 92UG037.8, CZA97.012 gp120 lacks a glycan at residue 295. This glycan site is generally considered to be one of the principal components of the 2G12 epitope (58)(59)(60)(61)(62)(63). Nonetheless, we observed that 2G12 could still bind efficiently to the CZA97.012 Env proteins in the SPR assay (Fig.…”
Section: Resultsmentioning
confidence: 71%
“…91 Furthermore, Dacheux and colleagues have studied the antigenicity and exposure of critical neutralizing epitopes recognized by 2F5, b12 and 2G12 mAbs in 94 full length Env clones present during the early infection and at least 4 years later in four HIV-1 clade B infected patients. 92 Minor exposure differences were observed for 2F5 and b12 epitopes in early isolates versus late isolates. However, Env glycoprotein of the HIV-1 quasi species present during the primary infection did not expose the 2G12 neutralizing epitope.…”
Section: Cd4 Inducible (Cd4i) Conformational Epitopes In Gp120mentioning
confidence: 99%
“…HIV-1 has evolved multiple mechanisms to shield the conserved epitopes from binding of neutralizing antibodies. The exposed surface of gp120 is heavily glycosylated, with a continuous shift in vivo of the sugar moiety positions, generating a protective dynamic glycan shield preventing antibody binding by steric hindrance (5,9,29,37).…”
mentioning
confidence: 99%
“…It binds to a cluster of high-mannose glycans, with ␣132 terminal mannose residues as essential components (31,32,33,35). Characterization of the 2G12 epitope through extensive sitedirected mutagenesis studies on prototype subtype B strains showed the implications of three major potential N-glycosylation sites (PNGS) at positions 295, 332, and 392 that are critical for 2G12 binding and two additional N-glycans at positions 339 and 386 that likely play indirect roles (9,31,32,35). The crystal structures of Fab 2G12 revealed an unusual structure with swapped variable domains that allow it to make multivalent interactions matching the geometrical constraints for recognition of the carbohydrate cluster (6,7).…”
mentioning
confidence: 99%